118k views
0 votes
G(x) = x-6
If the opposite of g(x) is -g(x),
then -g(x) =

User Nico Diz
by
5.1k points

2 Answers

3 votes

Answer:

-x+6

Step-by-step explanation: edge 2020

User Anish Sapkota
by
4.9k points
4 votes

Answer: The required expression for -g(x) is -x+6.

Step-by-step explanation: We are given the following function :


g(x)=x-6.

Also, the opposite of g(x) is -g(x).

We are to find the expression for g(x).

According to the given information, we have


-g(x)\\\\=-(x-6)\\\\=-x+6.

Thus, the required expression for -g(x) is -x+6.

User Michael Lukin
by
4.7k points